2012
DOI: 10.1155/2012/634195
|View full text |Cite
|
Sign up to set email alerts
|

Role of Vitamin D in Insulin Resistance

Abstract: Vitamin D is characterized as a regulator of homeostasis of bone and mineral metabolism, but it can also provide nonskeletal actions because vitamin D receptors have been found in various tissues including the brain, prostate, breast, colon, pancreas, and immune cells. Bone metabolism, modulation of the immune response, and regulation of cell proliferation and differentiation are all biological functions of vitamin D. Vitamin D may play an important role in modifying the risk of cardiometabolic outcomes, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
193
0
18

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(230 citation statements)
references
References 104 publications
6
193
0
18
Order By: Relevance
“…It appears to enhance insulin sensitivity through different mechanisms [55]. Further, vitamin D deficiency has been shown to activate inflammation, cytokine release, upregulation of nuclear factor κB and tumor necrosis factor α, and to raise serum levels of parathyroid hormone [47,56]. Recent studies have found a strong link between vitamin D deficiency, obesity and metabolic syndrome [57].…”
Section: Vitamin Dmentioning
confidence: 99%
“…It appears to enhance insulin sensitivity through different mechanisms [55]. Further, vitamin D deficiency has been shown to activate inflammation, cytokine release, upregulation of nuclear factor κB and tumor necrosis factor α, and to raise serum levels of parathyroid hormone [47,56]. Recent studies have found a strong link between vitamin D deficiency, obesity and metabolic syndrome [57].…”
Section: Vitamin Dmentioning
confidence: 99%
“…25 Vitamin d is also thought to play an important role in insulin resistance and glucose homeostasis 26 and it has been proposed that vitamin d supplementation may be an effective addition to the standard treatment of obesity and its associated insulin resistance. 27 a couple of decades ago, four small studies 28 …”
Section: Obesity and Weight Management Vitamin Dmentioning
confidence: 99%
“…Vitamin D has in vitro and in vivo effects on pancreatic β-cells and insulin sensitivity. [5] A meta-analysis was conducted recently to find out the association of vitamin D status and cardiometabolic disorders (cardiovascular disease, diabetes, and metabolic syndrome) which reviewed 28 independently published studies. The findings showed a significant 55% reduction in the risk of diabetes (9 studies), a 33% reduction in the risk of cardiovascular diseases (16 studies), and a 51% reduction in metabolic syndrome (8 studies) associated with a high serum 25-dihydroxy vitamin D (25(OH) D) concentration.…”
Section: Introductionmentioning
confidence: 99%